THE GLOBAL LANDSCAPE IS FERTILE GROUND FOR TERRORIST RADICALIZATION (Security Dialogues, 2024)
The article deals with broadening the view of terrorist radicalization, starting fromthe causes that lead to terrorist radicalization, through social media as a friend of terroristpropaganda distribution, and up to the migration to the dark side of the Internet. The currentglobal landscape is affected by multiple recent crises and largely with high uncertainty,this combined with overall hyper-connectivity is a fertile ground for terrorist radicalization.The impact that terrorists have is due to the spread of their narrative through the media,distributing propaganda material that is easily accessible to all. This material remainsavailable and a potential risk for the spread of new recruits. The online environment is a keymedium for terrorist propaganda where law enforcement agencies are forced to take deepersteps to deal with disinformation and propaganda spread by terrorist organizations, which inturn forces terrorists to change their structure and modus operandi.
Keywords: Terrorism, radicalization, social media, anonymous platforms, dark web